1947
DOI: 10.1111/j.1467-6494.1947.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Asch on "Forming Impressions of Personality": Further Evidence

Abstract: In a recent study of the processes involved in the forming of impressions of personality, Asch concluded that this formation "is an organized process, that charactenstics are perceived in their dynamic relations, that certain qualities are discovered, leading to the distinction between them and peripheral qualities, that relations of harmony and contradiction are observed To know a person is to have a grasp of a particular structure "Â s Asch has pointed out, there have been several theories regarding the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

1960
1960
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…8) and by Bruner and Tagiuri (1954) and need no further comment here. Asch's direct findings seem quite reliable and have been confirmed in several studies (e.g., Mensh & Wishner, 1947).…”
Section: Introductionsupporting
confidence: 57%
“…8) and by Bruner and Tagiuri (1954) and need no further comment here. Asch's direct findings seem quite reliable and have been confirmed in several studies (e.g., Mensh & Wishner, 1947).…”
Section: Introductionsupporting
confidence: 57%
“…This would give rise to the halo effect. His work was clarified by Mensh and Wishner (1947), who showed that context had an effect on ratings and thus on the halo effect. Cooper (1981) noted that the magnitudes of the intercategory correlations are due to both true intercorrelations between categories and illusory theories held by raters regarding the extent to which categories are related to one another.…”
Section: Examples Of Constructs With a Dgfmentioning
confidence: 99%
“…The results suggest that changing a trait from positive (e.g., warm) to negative (e.g., cold) made the overall impression more negative (negative traits of the pairs were chosen more frequently). Though this effect has been replicated repeatedly (e.g., Mensh & Wishner, 1947;Veness & Brierley, 1963;Semin, 1989), it may not provide the most stringent test of the primacy-of-warmth hypothesis, as changing any positive trait into a negative one is likely to influence the overall valence of the trait-list.…”
Section: Interpretations Of Asch's Workmentioning
confidence: 99%
“…Consequently, the interpretation of these data was heavily contested by his contemporaries (e.g., Gollin, 1954;Luchins, 1948). Because replications of Asch's research did not include systematic analysis of open-ended responses either (e.g., Mensh & Wishner, 1947;Semin, 1989;Veness & Brierley, 1963), as yet it is unclear to what extent they provide evidence for primacyof-warmth (or for effects that were the actual focus of Asch's paper; more information on those effects is available in our Additional Findings).…”
Section: Interpretations Of Asch's Workmentioning
confidence: 99%